Development of RPG-Based Mathematics Educational Games with the Waterfall Method on Fraction Material for Elementary School Students - Satriyo, Azis; Azis, Abdul; Saputri, Fiqih Hana; Ferawati, Ferawati (Sinkron : jurnal dan penelitian teknik informatika, 2025)
Mathematics is one of the subjects that plays an important role in everyday life and in developing logical thinking and problem-solving skills. One of the topics that often poses a challenge for elementary school students is fraction numbers. Fractions are often considered an abstract and difficult concept to understand because they involve numerical representations that differ from whole numbers. This difficulty frequently leads to a lack of interest in learning mathematics, ultimately affecting students' academic performance. The data collection stages applied include interviews, observations, and the distribution of questionnaires. The development of this learning media follows the Waterfall model, which aims to design improvements to the existing system. The results of the User Acceptance Test reveal that this game received a user perception score of 90.5%, categorizing it as "very good," indicating that students find it both enjoyable and effective as a learning tool. This suggests that the game is not only engaging but also effective in helping students understand fraction concepts in a more interactive and enjoyable way. With the presence of story elements, challenges, and engaging game mechanics, students can learn in a more immersive manner compared to conventional methods. Therefore, this game is suitable for use as a mathematics learning tool, particularly in understanding fraction operations such as addition, subtraction, multiplication, and division.